THE LEVEL OF EMPLOYING EDUCATIONAL TECHNOLOGY BY BASIC EDUCATION TEACHERS IN LIGHT OF TOTAL QUALITY STANDARDS IN THE DIRECTORATE OF EDUCATION OF UNIVERSITY DISTRICT - Faten Abdalkareem Alsmadi (INJOSEDU: International Journal of Social and Education, 2026)
This study aimed to investigate the level to which male and female basic education teachers employ educational technology in light of total quality standards within the Directorate of Education of the University District, and to examine differences according to gender, academic qualification, and years of experience during the first semester of the 2025/2026 academic year. The study adopted a descriptive survey design and utilized a questionnaire as the data collection instrument. The questionnaire comprised four main domains: learning objectives and competencies, assessment and measurement, educational materials and technology use, and learner support, accessibility, and interaction. These domains included 27 items, measured on a five-point Likert scale. The study sample consisted of 826 teachers, 39.9% male and 60.1% female, selected through simple random sampling. The results indicated that the overall level of technology use was high. Among the domains, assessment and measurement ranked first, followed by learner support, accessibility, and interaction, while learning objectives and competencies, and educational materials and technology use ranked lowest. The findings also revealed statistically significant differences in favor of female teachers, whereas no significant differences observed regarding academic qualification or years of experience. The researcher recommends leveraging female teachers’ commitment to closely monitoring the educational process, providing continuous feedback, and creating interactive learning environments